Amended Classification of the Open Abdomen. (March 2016) - Björck, M.; Kirkpatrick, A. W.; Cheatham, M.; Kaplan, M.; Leppäniemi, A.; De Waele, J. J.
Background: In 2009, a classification system for the open abdomen was introduced. The aim of such a classification is to aid the (1) description of the patient's clinical course; (2) standardization of clinical guidelines for guiding open abdomen management; and (3) facilitation of comparisons between studies and heterogeneous patient populations, thus serving as an aid in clinical research. Methods: As part of the revision of the definitions and clinical guidelines performed by the World Society of the Abdominal Compartment Syndrome, this 2009 classification system was amended following a review of experiences in teaching and research and published as part of updated consensus statements and clinical practice guidelines in 2013. Among 29 articles citing the 2009 classification system, nine were cohort studies. They were reviewed as part of the classification revision process. A total of 542 patients (mean: 60, range: 9–160) had been classified. Two problems with the previous classification system were identified: the definition of enteroatmospheric fistulae, and that an enteroatmospheric fistula was graded less severe than a frozen abdomen. Results: The following amended classification was proposed: Grade 1, without adherence between bowel and abdominal wall or fixity of the abdominal wall (lateralization), subdivided as follows: 1A, clean; 1B, contaminated; and 1C, with enteric leak. An enteric leak controlled by closure, exteriorization into a stoma, or a permanent enterocutaneous fistula is considered clean. Grade 2, developing fixation, subdivided as follows: 2A, clean; 2B, contaminated; and 2C, with enteric leak. Grade 3, frozen abdomen, subdivided as follows: 3A clean and 3B contaminated. Grade 4, an established enteroatmospheric fistula, is defined as a permanent enteric leak into the open abdomen, associated with granulation tissue. Conclusions: The authors believe that, with these changes, the requirements on a functional and dynamic classification system, useful in both research and training, will be fulfilled. We encourage future investigators to apply the system and report on its merits and constraints.